Distraction in verbal short-term memory: Insights from developmental differences - Elliott, Emily M.; Hughes, Robert W.; Briganti, Alicia; Joseph, Tanya N.; Marsh, John E.; Macken, Bill (Journal of memory and language, 2016)
•Studied vulnerability of verbal STM to auditory distraction in adults and children.•Rehearsal underpins some distraction regardless of developmental stage.•Poor attentional control also plays a substantial role in children’s distractibility.•Results support duplex- over unitary-mechanism accounts of auditory distraction. The contribution of two mechanisms of auditory distraction in verbal serial short-term memory—interference with the serial rehearsal processes used to support short-term recall and general attentional diversion—was investigated by exploiting differences in auditory distraction in children and adults. Experiment 1 showed that serial rehearsal plays a role in children’s as well as adults’ distractibility: Auditory distraction from irrelevant speech was greater for both children and adults as the burden on rehearsal increased. This pattern was particularly pronounced in children, suggesting that underdeveloped rehearsal skill in this population may increase their distractibility. Experiment 2 showed that both groups were more susceptible to changing- than steady-state speech when the task involved serial rehearsal—indicating that both groups suffer interference-by-process—but that children, but not adults, were also susceptible to any sort of sound (steady or changing) in a task thought to be devoid of serial rehearsal. The overall pattern of results suggests that children’s increased susceptibility to auditory distraction during verbal short-term memory performance is due to a greater susceptibility to attentional diversion; in this view, under-developed rehearsal-skill increases children’s distractibility by exacerbating their under-developed attentional control rather than by increasing interference-by-process.